The future heritage of artificial landscape; challenging the concept of aesthetics and exploring identity in the reinterpretation of industrial entities - Benek, Maksymilian; Suszczak, Aleksandra (My University, 2025)
With the contemporary world becoming more conscious of the choices made concerning use of natural resources, industrial areas are going through a shift of perception, and their future is uncertain. As they are examined, a question is posed whether they represent heritage, lives of the former generations, or are simply parts of a rather regrettable past. The purpose of this master thesis was to investigate the potential shift in perception of post-industrial spaces and prove that they should be considered as future heritage. It has aimed to challenge the commonly accepted idea of aesthetics and find appealing qualities in the artificial landscapes created due to human activities. It concentrated on the reinterpretation and readaptation of post-industrial structures and emphasized the need for new nature in those areas. The project area was located in the city center of Gothenburg, focusing on Rosenlundsverket - a power plant located on the riverbank of Göta Älv. By conducting multiple site visits and collecting accessible archival material, the site and its context were analyzed, treating Rosenlundsverket and its surrounding landscape as one entity. Utilizing the research by design method, volume studies have been conducted, determining the most suitable design option for the site. Reference projects were treated as case studies, and design methods present in them were transferred into the design. With the aid of transformation theories, a new narrative was suggested for Rosenlundsverket. The proposed reinterpretation of the building suggested exploring it as a part of the public realm and reintegrating it with nature. The thesis has also proposed new functions for the existing building in the form of an art museum and a club, with the contemporary additions complementing them with art studios and an auditorium. The landscape design took the form of a park situated around Rosenlundsverket and proposed a new nature design language for the city. The design proposal is represented in the form of drawings and visualizations that emphasize the design concept and contrast between old and new. The design proposes a space that should be for all, making heritage tangible and approachable while simultaneously enhancing the identity of Rosenlundsverket and carrying it further into the future.
Keywords: identity, heritage, artificial, landscape, reuse